Synergistic Inhibition of Plantaricin E/F and Lactic Acid Against Aeromonas hydrophila LPL-1 Reveals the Novel Potential of Class IIb Bacteriocin - Wang, Yang; Wei, Yunlu; Shang, Nan; Li, Pinglan (Frontiers in Microbiology, 2022)
Plantaricin E/F (PlnEF) is a pair of two-component class IIb bacteriocin produced by lactic acid bacteria. PlnEF commonly displays potent antimicrobial activity against certain Gram-positive organisms. In this study, we investigated the synergistic activity of PlnEF combined with lactic acid against Gram-negative food and aquaculture potential pathogen Aeromonas hydrophila LPL-1, which is naturally resistant to PlnEF. We applied SDS-PAGE, wavelength-scanning, laser confocal microscopy, flow cytometer, scanning electron microscopy (SEM), transmission electron microscopy (TEM), and two-dimensional electrophoresis to investigate their synergistic inhibitory activities. The results showed that L-lactic acid drove the release of LPS from A. hydrophila, making it possible for PlnEF to contact the inner cell membrane of A. hydrophila. Besides, co-treatment of lactic acid and PlnEF caused severe morphological and intracellular changes of A. hydrophila, including blebs on the cell surface, abnormal cell elongation, inner membrane disruption, pore-forming through the outer and inner membrane, coagulation of the cytoplasm, and structural transformation of DNA. Protein profile analysis revealed that combined treatment of lactic acid and PlnEF inhibited the energy metabolism, protein synthesis, protein folding, and DNA replication in A. hydrophila. These findings proved that PlnEF combined with lactic acid was efficient against A. hydrophila and shed light on bacteriocin's potential and a new inhibition mechanism against A. hydrophila. Importance: Bacteriocins and their producing strains are increasingly used to substitute artificial preservatives and antibiotics in the food and aquaculture industries. However, the bacteriocins produced by lactic acid bacteria are efficient to mainly Gram-positive bacteria. Our paper had demonstrated the antimicrobial activity of class IIb bacteriocin against potential Gram-negative pathogen, A. hydrophila LPL-1, when combined with lactic acid. The results could refresh our knowledge about the potential of class IIb bacteriocins produced by lactic acid bacteria.